Respuestas
Respuesta dada por:
22
Tenemos.
Arita(a) = 2a - 1
Volumen = arista³
Volumen = ( 2a - 1)³ Aplicas. (a - b)³ = a³ - 3a²b +3ab² - b³
Volumen = (2a)³ - 3(2a)²(1) + 3(2a)(1)² - 1³
Volumen = 2³a³ - 3(2²a²) + 6a - 1
Volumen = 8a³ - 3(4a²) + 6a - 1
Volumen = 8a³ - 12a² + 6a - 1
Respuesta.
8a³ - 12a² + 6a - 1
Arita(a) = 2a - 1
Volumen = arista³
Volumen = ( 2a - 1)³ Aplicas. (a - b)³ = a³ - 3a²b +3ab² - b³
Volumen = (2a)³ - 3(2a)²(1) + 3(2a)(1)² - 1³
Volumen = 2³a³ - 3(2²a²) + 6a - 1
Volumen = 8a³ - 3(4a²) + 6a - 1
Volumen = 8a³ - 12a² + 6a - 1
Respuesta.
8a³ - 12a² + 6a - 1
Preguntas similares
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 10 años
hace 10 años